Better floors, better health: a theory of change for an improved household flooring intervention in rural communities in Kwale and Bungoma counties, Kenya - Stella Kepha; Hugo Legge; Katherine E. Halliday; Victoria Ochwal; Lynne Elson; Jacinta Mwongeli; William E. Oswald; Beatrice Kakoi; James Wambua; Charles Mwandawiro; Ulrike Fillinger; Rachel Pullan; et al. (BMC Public Health, 2025)
Abstract Background Household flooring is increasingly being investigated as a determinant of health, however the pathways through which flooring may impact health and wellbeing are not yet well understood. The SABABU study is a cluster-randomised controlled trial evaluating the impact of an improved flooring intervention on soil-transmitted helminthiasis, tungiasis, and enteric infections in Bungoma and Kwale counties, Kenya. This paper presents the findings from a theory of change development process that was undertaken as part of the formative research phase of the SABABU project. Methods A co-creation workshop (n = 1), stakeholder meetings (n = 2), and community meetings (n = 2) were held with a range of participants including community members (n = 36), village-level leaders (n = 28), and local government stakeholders (n = 14) to draft and refine the theory of change framework. These meetings were informed by a previous formative research phase conducted in study communities – comprised of household observations, in-depth interviews, and focus group discussions with community members – to investigate daily routines, use of space within homes, and attitudes towards home improvement. Results The theory of change framework demonstrates how the improved household flooring intervention aims to reduce prevalence of soil-transmitted helminthiasis, enteric infections and tungiasis and improve psychological wellbeing among children and caregivers. Reductions in infections are predicated on limited contact between improved floors and animals, regular floor cleaning, and household members conducting their daily routines on the new floors. Gains in psychological wellbeing are tied to increased feelings of pride, self-efficacy, and social progress, as well as improved quality of life through reduced morbidity from enteric and parasitic infections. Conclusion This study presents a theory of change framework mapping the pathways through which an improved flooring intervention may impact health and wellbeing. The results can be of use to researchers or programmes that are in the design or evaluation phase of a household flooring project in Kenya or other settings where access to improved floors is limited.